Fluoro-18-fluorodeoxyglucose positron emission tomography/computed tomography detects Ewing’s sarcoma of the larynx with multiple distant bone metastases: a case report and literature review - Hu, Xianwen; Liao, Yan; Wang, Rui; Wen, Rui; Li, Dandan; Wang, Pan; Cai, Jiong (Frontiers in Medicine, 2023)
Ewing sarcomas (EWS) are highly malignant neoplasms of mesenchymal origin that are rare in the head and neck. Only a few laryngeal EWS have been reported in the literature. We report a 47 years-old man who visited our hospital for medical help after 5 months of hoarseness and sore throat. Computed tomography (CT) showed uneven thickening of the epiglottis fold, right vocal cord, and anterior union. In addition, fluoro-18-fluorodeoxyglucose positron emission tomography (18F-FDG PET)/CT has confirmed high activity in the already known laryngeal and nodal lesions, and has revealed otherwise unknown skeletal metastases. We also reviewed the published clinical features, histopathology, and imaging findings of nine patients with laryngeal EWS confirmed by pathology. The main clinical manifestations of laryngeal EWS are rapidly growing lumps, hoarseness, acute respiratory distress, and aphonia. The EWS tumor cells usually express CD99, vimentin, synaptophysin (Syn), and neuron-specific enolase (NSE) but do not express common antigen (LCA), CD20, and chromaffin granin (CgA). Laryngeal EWS’ CT imaging characteristics are mainly homogeneous, well-bounded soft-tissue masses. Our case suggests that EWS should be considered a differential diagnosis of laryngeal cancer, especially when PET/CT reveals distant bone metastasis, which is more likely to indicate EWS.